Motivational Teaching Strategies and Their Impact on Students’ Writing Performances - Nurul Fachrunnisa; Novalia Tanasy; Andi Khaerun Niza; A. Ilah Nurul Falah; Isnaeni Wahab (Universitas Islam Negeri Palopo, 2025)
This study investigated the effect of motivational teaching strategies on the writing abilities of EFL students. This study involved 15 students in the English Education study program of Universitas Muslim Maros, Indonesia. By employing a qualitative approach, the study utilised semi-structured interviews and classroom observations to gather data, which were then analysed using thematic analysis. The results showed that lecturers’ use of motivational teaching strategies had a major effect on students’ writing, including increased confidence and willingness to write, enhanced engagement and interest in writing, developed critical thinking and creativity, as well as improved writing proficiency. Direct observation in the classroom also demonstrated how lecturers’ strategies encouraged students to write critically and creatively, which enhanced their writing performances. The findings of this study concluded that motivational teaching strategies act as a key role in enhancing EFL students’ writing performance. It offers valuable insights for teaching practices in Indonesian higher education contexts.